Al-Ashoosh: a third-millennium BC desert settlement in the United Arab Emirates. (21st November 2016) - Contreras, F.; Carcacer, N.; Thomas, J.; Koljic, D.; Murray, M.; Bukhash, R.M.; Al Abbar, S.O.; Boraik, M.; Zein, H.M.
Abstract : The archaeological site of Al-Ashoosh is a third-millennium BC settlement located in the Rub al-Khali Desert (or Empty Quarter), 70km south of Dubai in the United Arab Emirates (UAE) (Figure 1 ). This site provides an excellent example of the type of occupation of the inland deserts of the Oman peninsula during the period following the Holocene Climatic Optimum. Between November 2015 and May 2016, the Dubai Municipality and the Sanisera Archaeology Institute conducted excavations at the site of Al-Ashoosh. This site was discovered during two seasons of survey in 2002–2003. This survey work, undertaken by the Dubai Municipality and the Department of Antiquities of Jordan, identified 33 archaeological sites ranging in date from prehistory to the late Islamic period. In 2006–2007, more-detailed archaeological investigations of the area of Al-Ashoosh were conducted, including survey, excavation and geological sampling (Casana et al. 2009 ; Herrmann2012 ; Contreras & Carcacer2016 ).